التزام جراح التجميل بالتبصير - سي يوسف كجار, زاهية حورية (University of Eloued جامعة الوادي, 2020)
يعد التزام بالتبصير من الالتزامات الأساسية الملقاة على عاتق الطبيب بشكل عام وعلى الجراح التجميلي بشكل خاص. إذ لا يصدر رضا صحيحا ومستنيرا من الزبون المريض إلاّ بعد تبصيره. ونظرا للخصوصية التي تتميز بها الجراحة التجميلية، فإن الالتزام بالتبصير لا يقتصر على إعلام المريض بمخاطر العملية المتوقعة فقط، بل حتى بالنسبة للمخاطر التي تحدث نادرا أي استثنائية. وهو التزام بتحقيق نتيجة يفرض على الجراح التجميلي بهدف إعادة التوازن المعرفي بينه وبين المريض، وبالتالي فالإخلال به يرتب المسؤولية. Enlightening the patient is one of the most important obligations that the doctor in general and the plastic surgeon in particular should adhere to. The consent of the patient is not deemed valid and conscious unless the patient is well advised. Because of the particularity that characterizes plastic surgery, enlightening the patient is not restricted to informing him about the risks expected, but also the risks that happen rarely meaning the exceptional ones. This obligation is imposed upon the surgeon and it aims at restoring the balance between him and his patient, therefore breaching it results in accountability.
مجلد11، عدد3
Keywords: جراح التجميل؛ تبصير؛ المريض؛ المخاطر؛ المسؤولية; Plastic surgeon; Enlightening; Patient; Risks; Responsibility